"It is like you are in a golden cage": How autistic students experience special education classrooms in general high schools. (March 2023) - Zakai–Mashiach, Mati
Abstract: Background: Students with autism spectrum disorder (ASD) often grapple with the challenges and demands of a general school environment. To date, studies have focused on inclusion within that environment, not distinguishing the experience of students in ASD special education classrooms within the general school. This study examined the retrospective perceptions of high-functioning autistic high school graduates who had been in ASD special education classrooms in general high schools to understand their experience, learn about their needs, and enhance future educational experiences. Method: Using interpretative phenomenological analysis (IPA) as a methodological framework, semi-structured interviews were conducted with 12 autistic individuals aged 19–27 that were enrolled in those particularized classrooms during high school. Data were analyzed using Thematic Analysis. Results: Three overarching themes were identified: (1) the challenge of heterogeneity among students in these classrooms; (2) exclusion and labeling; and (3) identity confusion. Conclusions: The findings of this paper highlight the need for greater attention to the voices and experiences of individuals with ASD regarding this educational model of ASD special education classrooms in general schools. Participants' perceptions about their educational experience in ASD special education classrooms need to be addressed at all levels of inclusive policy and practice. Highlights: Retrospective-study participants had been high-functioning ASD high-schoolers. Small ASD classes were too heterogenous for high-functioning participants. Small ASD-classes can lead to isolation, academic and emotional challenges. Small ASD-class placement in general schools can lead to identity confusion. Schools must hear and respond to ASD students' class placement preferences.